Factors Related To The Standard Of Care And Installation Of A Dower Cateter In A Hospital - mohamad judha (Akper Kesdam I/Bukit Barisan Padang, 2020)
Background: Urethral catheter placement is a form of nursing care performed by nurses, a standard for catheter placement is required. Urinary tract infections often occur around 40% of all hospital infections each year. In addition, from some researchers, 80% of urinary tract infections occur due to the use of catheterization instruments, because almost 10% of all hospitalized patients, at Bantul Hospital in 2017 There are 21% of patients are infected with the urinary tract. Nurse compliance uses standards based on various factors. Research Objectives: To determine the factors associated with the participation of nurses in the implementation of the standard installation of urethral catheters Research Methods: Descriptive analytic research by discussing the cross-sectional study. The sample used was total sampling with a sample of 43 nurses according to inclusion criteria. Data collection tools using questionnaires and observation sheets. Chi-Square data analysis with α <0.05. Results: The gender of female respondents was 76.7%. Age of respondents received 18-40 years 76.7%. The level of knowledge of respondents in the good category is 65.1%. The attitude of respondents in the positive category was 83.7%. The working period of respondents <5 years 51.2%. There is a significant relationship to age with the implementation of the standard implementation of urethral catheters, (P = 0.003 with an OR value of 2.54). There is a significant relationship between knowledge and the implementation of standard urethral catheter placement (P = 0,000 with an OR value of 19.50). There is a significant relationship between attitude with the agreement on the implementation of the standard urethral catheter installation (P = 0.007 with an OR value of 0.361). There is a significant relationship between a work period and the implementation of the standard implementation of urethral catheters (P = 0,000 with an OR value of 20.40). Conclusion: There is a significant relationship between age, knowledge, attitudes, and years of service to the approval of nurses in the implementation of the standard installation of urethral catheters in care in Bantul Hospitall Keywords: Working period of a nurse, and catheter installation standards